Retorika Dakwah Imperatif Sebagai Pembentuk Karakter Mahasiswa - Faizah, Umi; Saddhono, Kundharu (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2015)
Islamic propaganda rhetoric is one of the basic competencies in the course of rhetoric at the University of Muhammadiyah Purworejo. Rhetoric as the study of science communication is still a concern. The purpose of this article is to describe the islamic propaganda rhetoric, imperative islamic propaganda rhetoric and character formation of students Muhammadiyah Purworejo University. Data were analyzed and the results of a descriptive analysis, a phenomenon which is not the form of numbers or the coefficient of correlation between the variables. The population in this study is the fourth semester students of academic year 2015/2016. Samples were taken from each class in islamic propaganda rhetoric containing imperative speech. Islamic propaganda rhetoric is the art of delivering (news), conveying information, calling, giving warning about Islam correctly. Imperatives islamic propaganda rhetoric of students are able to realize the character education among others: Religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, nationality spirit, love the homeland, rewarding achievements, friendly/communicative, peaceful , fond of reading, environmental care, social care and responsibility